Zooming in - zooming out: politics of photographic aesthetics across Finnish-Soviet borders in the 1930s - Ristolainen, Mari (Nordlit, 2014)
This article discusses ‘visual bordering processes’ and the aesthetic strategies used in border photographs. The two main objectives are, firstly, to discuss the politics of aesthetic strategies in photographical process of border-building and/or border-unbuilding in Soviet and Finnish photographs of the 1930s. Secondly, the aim is to show how the different aesthetics strategies of establishing and disestablishing ‘the other side’ create ambivalences about the border existence in the photographs studied. This article forms a comparative position on Finnish and Soviet border communities of the pre-II-World-War Finland and Soviet Union in the late 1930s. The aim is to draw a parallel between how photographic publications perceive and discursively construct borders and the aesthetic strategies used in the pictures themselves. I seek to show how the national border divides aesthetic strategies used in photographs. The studied photographs are similar by themes, but show the border of reference codes between two aesthetical systems.